Postictal clinical and electroencephalographic activity following intracranially recorded bilateral tonic–clonic seizures. (21st December 2018) - Bateman, Lisa M.; Mendiratta, Anil; Liou, Jyun‐You; Smith, Elliot J.; Bazil, Carl W.; Choi, Hyunmi; McKhann, Guy M.; Pack, Alison; Srinivasan, Shraddha; Schevon, Catherine A.
Summary: Objective: The dynamics of the postictal period, which may demonstrate such dramatic clinical phenomena as focal neurological deficits, prolonged coma and immobility, and even sudden death, are poorly understood. We sought to classify and characterize postictal phases of bilateral tonic–clonic seizures based on electroencephalographic (EEG) criteria and associated clinical features. Methods: We performed a detailed electroclinical evaluation of the postictal period in a series of 31 bilateral tonic–clonic seizures in 16 patients undergoing epilepsy surgery evaluations for focal pharmacoresistant epilepsy with intracranial electrodes and time‐locked video. Results: The postictal EEG demonstrated three clearly differentiated phases as follows: attenuation, a burst‐attenuation pattern, and a return to continuous background, with abrupt, synchronized transitions between phases. Postictal attenuation was common, occurring in 84% of seizures in 94% of patients in this study. There was increased power in gamma frequencies (>25 Hz) during postictal attenuation periods relative to preictal baseline in 88% of seizures demonstrating the attenuation pattern (n = 25 seizures, P < 0.002). Such increases were seen in >90% of channels in 13 seizures (52%) and <10% of channels in three seizures (12%). Postictal immobility was seen in 87% of seizures, with either a flaccid (58%) or rigid/dystonic (29%) appearance. Clinical motor manifestations, including focal dystonic posturing, automatisms, head and eye deviation, and myoclonic jerking, continued or emerged within the first minute following seizure termination in 48% of seizures, regardless of EEG appearance. Significance: Intracranial postictal attenuation, which may be diffuse or focal, is so common that it should be regarded as a ubiquitous feature of bilateral tonic‐clonic seizures, rather than an unusual event. The prominence of high‐frequency activity coupled with emerging clinical features, including rigid immobility and semiologies such as automatisms, during the postictal period supports the presence of ongoing seizure‐related neuronal activity in unrecorded brain regions.